Alpha cluster resonance structure of light nuclei close to coulomb barrier - Nauruzbayev, D. K.; Nurmukhanbetova, A. K.; Mynbayev, N. A.; Golovkov, M. S.; Rogachev, G. V.; Tikhonov, A. V.; Koloberdin, M. V.; Ivanov, I. A.; Goldbergb, V. Z. (21st International Symposium on Heavy Ion Inertial Fusion. Autonomous Organization of Education “Nazarbayev University”, 2016)
The aim of this experimental study is to investigate the structure of the 19F nuclei at energies representing astrophysical interest. Here we study the resonant interaction 15N+4He in the cyclotron DC-60 in Astana.
Keywords: Alpha cluster resonance structure; Research Subject Categories::NATURAL SCIENCES::Physics